Serum Vitamin Levels, Cardiovascular Disease Risk Factors, and Their Association with Depression in Korean Women: A Cross-Sectional Study of a Nationally Representative Sample - Seon Mi Lee; Jong Chul Baek (Medicina, 2023)
Background and Objectives: Serum vitamin levels, cardiovascular disease risk factors, and their association with depression is a complex issue that has been the subject of much research. Therefore, we investigated the relationship between vitamin A, B9, and E levels, cardiovascular risk factors, and depression in premenopausal and menopausal South Korean women. Materials and Methods: This cross-sectional study used the 2016–2018 Korea National Health and Nutrition Examination Survey data. Depression was assessed using a questionnaire to check for symptoms of depression or the Patient Health Questionnaire–9. Blood samples were collected from the antecubital vein in the morning after an overnight fast. Covariates were defined as self-reported physician diagnoses. Well-trained medical staff performed the standard procedures. Statistical analysis was performed using the complex sample analysis method of SPSS, using two separate logistic regression models (model 1: adjusted for age; model 2: adjusted for age, marital status, smoking, and alcohol consumption). Results: A total of 3313 women aged over 20 years were enrolled. The association between vitamin A levels and depression was as follows: lower levels of vitamin A were associated with an increased risk of depression in premenopausal women in model 1 and model 2. The levels of serum vitamins E and B9 were not correlated with depression in premenopausal and postmenopausal women. In the premenopausal group, depression increased in the obesity (model 1: p = 0.037; model 2: p = 0.047) and diabetes mellitus (model 1: p = 0.010; model 2: p = 0.009) groups. The menopausal group with depression had higher rates of stroke (model 1: p = 0.017; model 2: p = 0.039) and myocardial infarction (model 1: p = 0.004; model 2: p = 0.008) than the group without depression. Conclusions: Depression is correlated with lower blood levels of vitamin A in premenopausal women. Vitamin B9 and E levels were not associated with depression independent of menopausal status. Depression is associated with obesity and diabetes mellitus in premenopausal women and with stroke and myocardial infarction in postmenopausal women.